Cu-Ag loaded nano-Cu x O-Ag2O composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202410429887.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-10
AI Technical Summary
但现有技术中用于降解有机物的光催化剂存在催化效率低,催化剂脱落、溶解和团聚的问题
[0050](1)本发明所述Cu-Ag负载纳米CuxO-Ag2O复合材料,包括多孔Cu-Ag载体和负载在所述多孔Cu-Ag载体表面的CuxO和Ag2O,具有多孔结构的Cu-Ag载体(作为基底)可生长出更精细的纳米CuxO,有助于提供更多的活性位点,并且载体的孔隙可调;Ag网络能够增强材料的电子导电性,有助于显著提高光催化降解的性能。原位生长的CuxO和Ag2O材料稳定性好,具有自支撑的特点,使用时便于取出,有利于重复利用。
Smart Images

Figure CN118403638B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalyst degradation of organic pollutants, specifically relating to a Cu-Ag supported nano-Cu x O-Ag2O composite materials, their preparation methods, and applications. Background Technology
[0002] Human society faces increasingly serious environmental problems, especially water pollution. Photocatalysis, as a green and clean water treatment technology capable of effectively mineralizing organic pollutants in water on-site, has received widespread attention. Currently, a crucial issue in the application of photocatalysis is how to ensure the effective recovery of the catalyst without loss or secondary pollution, as these nanoparticle catalysts (NPs) inevitably release into the water, posing a potential threat to the ecosystem. Nano-TiO2 is the most commonly used catalyst in photocatalytic reactions and has been shown to have certain toxicity to freshwater algae and other aquatic organisms.
[0003] To realize the environmentally friendly practical application of photocatalysis technology, photocatalyst immobilization technology has made rapid progress after several years of exploration, especially membrane immobilization technology. Therefore, membrane technologies with photocatalytic activity have attracted the attention of many researchers, particularly the widely studied application of the photocatalyst TiO2 in membrane technology. However, existing photocatalysts used for degrading organic matter suffer from low catalytic efficiency, catalyst shedding, dissolution, and aggregation problems.
[0004] Therefore, there is an urgent need to provide a catalyst with high catalytic efficiency for degrading organic pollutants. Summary of the Invention
[0005] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the present invention proposes a Cu-Ag supported nano-Cu... x O-Ag₂O composite material, its preparation method, and its application. The Cu-Ag supported nano-Cu of this invention... x O-Ag2O composite materials exhibit good catalytic degradation effects for photodegradation of organic pollutants (such as rhodamine b).
[0006] The inventive concept of this invention is as follows: The Cu-Ag supported nano-Cu of this invention x O-Ag₂O composite material, comprising a porous Cu-Ag support and Cu₂O loaded on the surface of the porous Cu-Ag support. x O and Ag₂O, with a porous Cu-Ag support (as a substrate), can grow finer nano-Cu. xO helps provide more active sites, and the porosity of the support is tunable; the Ag network enhances the electronic conductivity of the material, contributing to a significant improvement in photocatalytic degradation performance. In-situ grown Cu x O and Ag2O materials have good stability and self-supporting characteristics, making them easy to remove and reuse.
[0007] The first aspect of the present invention provides a Cu-Ag supported nano-Cu x O-Ag2O composite material.
[0008] A Cu-Ag supported nano-Cu x O-Ag₂O composite material, comprising a porous Cu-Ag support and Cu₂O loaded on the surface of the porous Cu-Ag support. x O and Ag2O, where 1≤x≤2.
[0009] According to some embodiments of the present invention, the Cu x O includes copper oxide and cuprous oxide.
[0010] According to some embodiments of the present invention, the Cu x O is a needle-like structure.
[0011] According to some embodiments of the present invention, the thickness of the porous Cu-Ag support is 20-60 μm, more preferably 30-50 μm.
[0012] A second aspect of the present invention provides Cu-Ag supported nano-Cu x Preparation method of O-Ag2O composite material.
[0013] A Cu-Ag supported nano-Cu x The preparation method of O-Ag2O composite material includes the following steps:
[0014] S1. Gallium is applied to the surface of Cu, and a Cu-Ga alloy is formed by the reaction.
[0015] S2. Ag is plated onto the surface of the Cu-Ga alloy obtained in step S1, and a Cu-Ga-Ag alloy is formed by the reaction.
[0016] S3. The Cu-Ga-Ag alloy obtained in step S2 is dealloyed to obtain a porous Cu-Ag substrate.
[0017] S4. Electrochemically oxidize the porous Cu-Ag substrate obtained in step S3 to obtain Cu-Ag-supported nano-Cu. x O-Ag2O composite material.
[0018] Liquid Ga has a low melting point and low toxicity, exhibiting good fluidity at room temperature and easily coated onto metal foil surfaces. It offers advantages such as safety and ease of preparation. While Hg is also a liquid metal at room temperature, it is toxic and unsafe. Furthermore, using Ga as an intermediate layer in the Cu-Ga-Ag alloy precursor leverages Ga's low melting point to effectively promote interdiffusion among Cu, Ag, and Ga, avoiding the extreme experimental conditions required by traditional high-temperature quenching.
[0019] According to some embodiments of the present invention, the specific process of preparing Cu-Ga alloy in step S1 includes: melting Ga and coating it on the surface of Cu, annealing it at 100-250°C to obtain Cu-Ga alloy.
[0020] Annealing temperature and annealing time affect the degree of solid-state diffusion reaction and the composition of the alloy phase formed. The higher the temperature and the longer the time, the thicker the alloy layer will be, and the phase formed will also change. Increasing the temperature helps the diffusion reaction more than extending the time, but as the thickness increases, the diffusion of the metal becomes more difficult.
[0021] According to some embodiments of the present invention, the annealing time is 1-12 hours, preferably 10-12 hours.
[0022] According to some embodiments of the present invention, the annealing temperature is 150-250°C, preferably 150-200°C.
[0023] According to some embodiments of the present invention, the thickness of the Cu-Ga alloy layer is approximately 1-20 μm. For example, 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, or 20 μm.
[0024] According to some embodiments of the present invention, step S2, depositing Ag on the surface of the Cu-Ga alloy, specifically includes the following steps: placing the Cu-Ga alloy under a vacuum of approximately 5 × 10⁻⁶. -5 Vapor deposition is performed within the Pa chamber, and the resulting alloy is then annealed. Vapor deposition can also be replaced by other methods, such as magnetron sputtering.
[0025] According to some embodiments of the present invention, the current during vapor deposition is set to 80-120A, more preferably 90-120A. The level of the vapor deposition current determines the level of the vapor deposition temperature; if it is too low, the metal will not turn into a gaseous state.
[0026] According to some embodiments of the present invention, the vapor deposition time is 2-3 hours, for example 2 hours, 2.5 hours, or 3 hours.
[0027] According to some embodiments of the present invention, the annealing temperature is 400-700°C, for example 400°C, 500°C, 600°C, or 700°C. More preferably, it is 400-450°C.
[0028] According to some embodiments of the present invention, the annealing time is 2-6 hours, more preferably 5-6 hours.
[0029] According to some embodiments of the present invention, step S3, the dealloying of the Cu-Ga-Ag alloy specifically includes the following steps: placing the Cu-Ga-Ag alloy in an acidic solution and heating it for corrosion treatment for 2-8 hours. Preferably, the corrosion treatment time is 3-6 hours.
[0030] Experiments have shown that, compared to the method of first thermally depositing Ag on the Cu foil surface and then coating it with Ga to prepare the precursor, the method of first coating Ga on the Cu foil surface and then thermally evaporating Ag results in a higher Ag content and a more uniform and regular distribution after dealloying, forming an Ag network structure on the substrate.
[0031] According to some embodiments of the present invention, the acidic solution comprises an HNO3 solution with a concentration of 0.5-1.5 wt.%.
[0032] Experiments revealed that HNO3 solution effectively completes the dealloying process, while hydrochloric acid and sulfuric acid are less effective. HF corrodes faster, but it is also more hazardous, and the faster dealloying rate leads to rapid Cu diffusion, causing dimensional coarsening or corrosion of the copper substrate, thus affecting the structure and properties of the final product. Therefore, this invention preferably uses HNO3 solution for dealloying.
[0033] According to some embodiments of the present invention, the temperature of the corrosion treatment is 25-60°C, more preferably 35-55°C.
[0034] The concentration of the HNO3 solution used for etching should not be too high, or the etching time should not be too long, in order to reduce or avoid the etching of the Cu substrate.
[0035] According to some embodiments of the present invention, the pore size of the porous Cu-Ag substrate obtained by dealloying is 100 nm-5 μm.
[0036] Preferably, in step S4, the electrochemical oxidation is constant current oxidation.
[0037] According to some embodiments of the present invention, step S4, the electrochemical oxidation of the porous Cu-Ag substrate specifically includes the following steps: placing the porous Cu-Ag substrate in an alkaline solution, performing constant current oxidation under a DC power supply for 5-15 minutes, washing and drying the obtained sample with pure water to obtain Cu-Ag-loaded nano-Cu. x O-Ag2O composite material.
[0038] According to some embodiments of the present invention, the alkaline solution is a sodium hydroxide or potassium hydroxide solution, for example, a 0.5-0.8 mol / L KOH solution.
[0039] According to some embodiments of the present invention, the porous Cu-Ag substrate in the DC power supply is the anode, and the platinum sheet electrode is the cathode.
[0040] According to some embodiments of the present invention, during the constant current oxidation process, the current density is 10-20 mA / cm². -2 More preferably 15-20 mA cm -2 The oxidation time is 5-15 min, more preferably 10-15 min.
[0041] Oxidation time and oxidation current will affect the oxidation of Cu. x The morphology of Cu nanoneedles changes with increasing oxidation time, oxidation current, and oxidation time. x The more O there is, the better Cu x The diameter of the O nanoneedles has increased.
[0042] According to some embodiments of the present invention, the Cu x O nanoneedles have a diameter of approximately 10-60 nm. For example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, or 60 nm.
[0043] According to some embodiments of the present invention, the pure water washing is repeated 2-5 times, for example 2 times, 3 times, 4 times, or 5 times.
[0044] According to some embodiments of the present invention, the drying time is 5-20 min, for example 5 min, 10 min, 15 min, 20 min.
[0045] A third aspect of the present invention provides a Cu-Ag supported nano-Cu x Applications of O-Ag2O composite materials.
[0046] The above Cu-Ag supported nano Cu x Application of O-Ag2O composite materials in photocatalytic degradation of organic matter.
[0047] According to some embodiments of the present invention, the organic compound includes rhodamine b.
[0048] According to some embodiments of the present invention, in the application, hydrogen peroxide solution is also added, with a mass concentration of 10-35%, preferably 25-30%.
[0049] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0050] (1) The Cu-Ag supported nano-Cu of the present invention x O-Ag₂O composite material, comprising a porous Cu-Ag support and Cu₂O loaded on the surface of the porous Cu-Ag support. x O and Ag₂O, with a porous Cu-Ag support (as a substrate), can grow finer nano-Cu. x O helps provide more active sites, and the porosity of the support is tunable; the Ag network enhances the electronic conductivity of the material, contributing to a significant improvement in photocatalytic degradation performance. In-situ grown Cu x O and Ag2O materials have good stability and self-supporting characteristics, making them easy to remove and reuse.
[0051] (2) The preparation method described in this invention is simple to operate, requires no toxic organic reagents during the preparation process, and is green and environmentally friendly; Ag2O is introduced and combined with a porous Cu-Ag substrate, while utilizing the good electronic conductivity of the Ag network structure and nano-Cu x O's abundant specific surface area structure generates a synergistic effect in photocatalysis, thereby developing highly efficient photocatalysts. The preparation method of this invention features mild reaction conditions, low process requirements, and a stable product structure, showing promising application prospects.
[0052] (3) Using the Cu-Ag supported nano-Cu described in this invention x O-Ag2O composite materials can be used as high-performance photocatalysts for the degradation of Rhodamine b, and have good application prospects in the field of photocatalytic degradation. Attached Figure Description
[0053] Figure 1 This is a SEM image of the porous Cu-Ag substrate obtained in step (3) of Example 1 of the present invention;
[0054] Figure 2 Cu-Ag supported nano-Cu prepared in Example 1 of this invention x SEM image of O-Ag2O composite material;
[0055] Figure 3 The XRD pattern of Cu-Ga alloy and Ag formed on the surface of Cu foil prepared in step (2) of Example 1 of this invention;
[0056] Figure 4 The XRD pattern of the porous Cu-Ag substrate obtained in step (3) of Example 1 of this invention;
[0057] Figure 5 Cu-Ag supported Cu nanoparticles prepared in Example 1 of this invention x XRD pattern of O-Ag2O composite material;
[0058] Figure 6 This is a comparison graph showing the time dependence of photocatalytic degradation of Rhodamine B in Example 1 of the present invention with that of other examples and comparative examples. Detailed Implementation
[0059] To enable those skilled in the art to more clearly understand the technical solutions described in this invention, the following embodiments are provided for illustration. It should be noted that the following embodiments do not constitute a limitation on the scope of protection claimed by this invention.
[0060] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are available from conventional commercial sources or can be obtained by existing known methods.
[0061] Example 1
[0062] A Cu-Ag supported nano-Cu x O-Ag₂O composite material, comprising a porous Cu-Ag support and Cu₂O loaded on the surface of the porous Cu-Ag support. x O and Ag₂O, Cu x O includes copper oxide and cuprous oxide.
[0063] A Cu-Ag supported nano-Cu x The preparation method of O-Ag2O composite material includes the following steps:
[0064] (1) Preparation of Cu-Ga alloy by solid-state diffusion reaction between metals: Cu foil (50 μm thick) was first rinsed with deionized water, then wiped with anhydrous ethanol to remove impurities, dried, and fixed on paper. Liquid metal Ga was coated on the outer surface of the Cu foil at a coating amount of 0.01 g / cm³. 2 After the entire coating is applied, the sample is left to stand for 10 minutes. Then, the sample is placed in a vacuum drying oven and heat-treated at 200°C for 12 hours to form a Cu-Ga alloy on the surface of the copper foil.
[0065] (2) Place the Cu-Ga alloy layer Cu foil prepared in step (1) into the thermal evaporation vacuum chamber, place the Ag target on the tungsten boat and wait for vacuum heating, and evacuate the vacuum chamber to 10. -5Heating begins again at the Pa level. The magnitude of the evaporation current is determined based on the vapor pressure of silver metal at this vacuum level. The current is set to 110A and the heating time is 2 hours. After the chamber cools down, the sample is taken out and placed in a tube furnace for annealing. The annealing temperature is set to 400℃ and the annealing time is 4 hours. This will form a Cu-Ga-Ag alloy on the Cu foil surface.
[0066] (3) The Cu foil with Cu-Ga-Ag alloy layer prepared in step (2) is subjected to chemical dealloying treatment: 1 wt.% HNO3 solution is selected and immersed at 40°C for dealloying for 4 hours to remove Ga. Then the dealloyed Cu foil is rinsed with deionized water and then vacuum dried to obtain porous Cu-Ag substrate.
[0067] (4) The porous Cu-Ag substrate obtained in step (3) was used to prepare Cu-Ag-loaded nano-Cu oxide and Ag oxide by constant current oxidation: constant current oxidation was used, with a platinum sheet electrode as the cathode and the porous Cu-Ag substrate as the anode. The electrolyte was a 0.5M KOH solution, and the oxidation was carried out at 20 mA cm⁻¹. -2 Nano-Cu was grown in situ on the surface of a porous Cu-Ag substrate by oxidation under constant current for 15 min. x O and Ag₂O, the sample was named Cu x After the reaction of O / Ag2O@NPC / Ag-15 is complete, rinse with deionized water, dry and store in a vacuum drying oven for later use.
[0068] Example 2
[0069] Cu-Ag supported nano-Cu x The preparation method of O-Ag2O composite material includes the following steps:
[0070] (1) Preparation of Cu-Ga alloy by solid-state diffusion reaction between metals: Cu foil (50 μm thick) was first rinsed with deionized water, then wiped with anhydrous ethanol to remove impurities, dried, and fixed on paper. Liquid metal Ga was coated on the outer surface of the Cu foil at a coating amount of 0.01 g / cm³. 2 After the entire coating is applied, the sample is left to stand for 10 minutes. Then, the sample is placed in a vacuum drying oven and heat-treated at 200°C for 12 hours to form a Cu-Ga alloy on the surface of the copper foil.
[0071] (2) Place the Cu-Ga alloy layer Cu foil prepared in step (1) into the thermal evaporation vacuum chamber, place the Ag target on the tungsten boat and wait for vacuum heating, and evacuate the vacuum chamber to 10. -5Heating begins again at the Pa level. The magnitude of the evaporation current is determined based on the vapor pressure of silver metal at this vacuum level. The current is set to 110A and the heating time is 2 hours. After the chamber cools down, the sample is taken out and placed in a tube furnace for annealing. The annealing temperature is set to 400℃ and the annealing time is 4 hours. This will form a Cu-Ga-Ag alloy on the Cu foil surface.
[0072] (3) The Cu foil with Cu-Ga-Ag alloy layer prepared in step (2) is subjected to chemical dealloying treatment: 1 wt.% HNO3 solution is selected and immersed at 40°C for dealloying, and the etching time is 4 h to remove Ga. Then the etched Cu foil is rinsed with deionized water and then vacuum dried.
[0073] (4) The porous Cu-Ag substrate obtained in step (3) was used to prepare Cu-Ag-loaded nano-Cu oxide and Ag oxide by constant current oxidation: constant current oxidation was used, with a platinum sheet electrode as the cathode and the porous Cu-Ag substrate as the anode. The electrolyte was a 0.5M KOH solution, and the oxidation was carried out at 20 mA cm⁻¹. -2 Nano-Cu was grown in situ on the surface of a multi-Cu-Ag substrate by oxidation under constant current for 5 min. x O and Ag₂O, the sample was named Cu x After the reaction of O / Ag2O@NPC / Ag-5 is complete, rinse with deionized water, dry and store in a vacuum drying oven for later use.
[0074] Comparative Example 1
[0075] Cu-supported nano-Cu x The preparation method of O material includes the following steps:
[0076] (1) Preparation of Cu-Ga alloy by solid-state diffusion reaction between metals: Cu foil (50 μm thick) was first rinsed with deionized water, then wiped with anhydrous ethanol to remove impurities, dried, and fixed on paper. Liquid metal Ga was coated on the outer surface of the Cu foil at a coating amount of 0.01 g / cm³. 2 After the entire coating is applied, the sample is left to stand for 10 minutes. Then, the sample is placed in a vacuum drying oven and heat-treated at 200°C for 12 hours to form a Cu-Ga alloy on the Cu foil surface.
[0077] (2) The Cu foil with Cu-Ga alloy layer prepared in step (1) is used to make porous Cu foil by chemical dealloying: 1M HNO3 solution is selected and soaked at 40℃ for dealloying, and the etching time is 4h to remove Ga. Then the etched Cu foil is rinsed with deionized water and then vacuum dried.
[0078] (3) The porous Cu foil obtained in step (2) was used to prepare Cu-loaded nano-Cu oxide by constant current oxidation: the constant current oxidation method was used, with a platinum sheet electrode as the cathode and the porous copper foil as the anode. The electrolyte was a 0.5M KOH solution, and the oxidation was carried out at 20 mA cm⁻¹. -2 Nano-Cu was grown in situ on the surface of porous Cu foil by oxidation under constant current for 15 min. x O, the sample was named Cu x After the reaction of O@NPC-15 is complete, rinse with deionized water, dry and place in a vacuum drying oven for later use.
[0079] Comparative Example 2
[0080] Cu-supported nano-Cu x The preparation method of O material includes the following steps:
[0081] (1) Preparation of Cu-Ga alloy by solid-state diffusion reaction between metals: Copper foil (50 μm thick) was first rinsed with deionized water, then wiped with anhydrous ethanol to remove impurities, dried, fixed on paper, and liquid metal Ga was coated on the outer surface of the copper foil at a coating amount of 0.01 g / cm³. 2 After the entire coating is applied, the sample is left to stand for 10 minutes. Then, the sample is placed in a vacuum drying oven and heat-treated at 200°C for 12 hours to form a Cu-Ga alloy on the Cu foil surface.
[0082] (2) The Cu foil with Cu-Ga alloy layer prepared in step (1) is used to make porous Cu foil by chemical dealloying: 1 wt.% HNO3 solution is selected and soaked at 40°C for dealloying, and the etching time is 4 h to remove Ga. Then the etched Cu foil is rinsed with deionized water and then vacuum dried.
[0083] (3) The porous Cu foil obtained in step (2) was used to prepare Cu-loaded nano-Cu oxide by constant current oxidation: the constant current oxidation method was used, with a platinum sheet electrode as the cathode and the porous copper foil as the anode. The electrolyte was a 0.5M KOH solution, and the oxidation was carried out at 20 mA cm⁻¹. -2 Nano-Cu was grown in situ on the surface of porous copper foil by oxidation under constant current for 5 min. x O, the sample was named Cu x After the reaction of O@NPC-5 is complete, rinse with deionized water, dry and place in a vacuum drying oven for later use.
[0084] Performance testing
[0085] 1. Microscopic morphology analysis
[0086] Surface morphology was analyzed using field emission scanning electron microscopy (SEM); phase composition was analyzed using X-ray diffraction (XRD).
[0087] Figure 1 The porous Cu-Ag substrate obtained in step (3) of Example 1; from Figure 1 It can be seen that the surface of the porous Cu-Ag substrate is a framework formed by silver, with a network structure formed by porous copper embedded inside.
[0088] Figure 2 Cu-Ag supported nano-Cu prepared in Example 1 x The SEM image of the O-Ag2O composite material shows that Cu-Ag supported on nano-Cu x The surface of the O-Ag2O composite material is covered with nano-needle-shaped Cu. x O covers the gaps where Ag forms channels.
[0089] Figure 3 The XRD pattern of Cu-Ga alloy and Ag formed on the surface of the Cu foil prepared in step (2) of Example 1 is shown. Figure 3 ("Intensity" indicates intensity, "degree" indicates degree, "Ag(PDF#04-0783)" refers to the standard card for Ag, and "CuGa2(PDF#25-0275)" refers to the standard card for CuGa2.) Clear diffraction peaks corresponding to the Cu-Ga alloy can be observed. In addition to the Cu-Ga alloy phase, diffraction peaks for Ag can also be observed, proving that the surface contains CuGa2 and Ag.
[0090] Figure 4 The image shows the XRD pattern of the porous Cu-Ag substrate obtained in step (3) of Example 1. Figure 4 ("Intensity" means intensity, "degree" means degree, "Ag(PDF#04-0783)" means standard card of Ag, "Cu(PDF#04-0836)" means standard card of Cu) You can see obvious diffraction peaks corresponding to copper. In addition, you can also see diffraction peaks of residual Ag, that is, the Ga element is corroded after dealloying (D in D-CuAgGa stands for Dealloying, which means that the dealloying precursor CuAgGa is dealloyed and there is no Ga after dealloying).
[0091] Figure 5 Cu-Ag supported Cu nanoparticles prepared in Example 1 x XRD pattern of O-Ag2O composite material, by Figure 5("Intensity" means strength, "degree" means degree, "CuO(PDF#045-0973)" means the standard card of CuO, "Cu2O(PDF#74-1230)" means the standard card of Cu2O, "Ag2O(PDF#17-0492)" means the standard card of Ag2O) See the composite material formed after oxidation, which has cuprous oxide, copper oxide and Ag2O phase.
[0092] 2. Photocatalytic performance analysis
[0093] Photocatalytic performance testing method: Prepare a 20ppm 50mL solution of Rhodamine B (a synthetic dye with a bright pink color), add 2mL of 30% hydrogen peroxide solution to the solution, place the obtained photocatalyst (the material prepared in the above examples and comparative examples as the photocatalyst) in a self-contained suspension device, suspend it in the solution, place a stir bar in the bottom beaker for stirring, and to prevent overheating, the beaker is equipped with water cooling to cool the internal solution. Use a PLS-SXE300 xenon lamp with a power of 300W for illumination, take samples every 1 minute, and analyze the results of each group of samples using a UV spectrophotometer. Repeat the experiment multiple times.
[0094] Figure 6 This is a comparison graph showing the time dependence of photocatalytic degradation of Rhodamine B in Example 1 of the present invention with that of other examples and comparative examples. Figure 6 In the text, "C / C0" represents the ratio of the concentration of rhodamine b at a certain time to the initial concentration of rhodamine b, which is used to measure the rate of rhodamine b degradation; "Time" represents time. Figure 6 In this context, "No H2O2" indicates that no H2O2 was added, and only the composite material prepared in Example 1 was added; "No catalysts" indicates that no photocatalyst was added, but H2O2 was added; "Cu x O@NPC-15” was prepared in response to ratio 1, and Cu-supported nano-Cu was prepared. x O material; "Cu" x Cu-loaded Cu nanoparticles prepared in response to ratio 2 of O@NPC-5” x O material; "Cu" x "O / Ag2O@NPC / Ag-15" corresponds to the Cu-Ag supported nano-Cu prepared in Example 1. x O-Ag2O composite material; "Cu x O / Ag2O@NPC / Ag-5” corresponds to the Cu-supported nano-Cu prepared in Example 2. xThe O-Ag2O composite material shows that the composite material containing silver oxide in Example 1 requires less time to degrade the same concentration of dye, as can be clearly seen from the concentration-time dependence curve. This indicates that the introduction of Ag2O helps to improve the degradation performance of the photocatalyst.
[0095] In addition, the composite material prepared in Example 1 required a shorter time to degrade Rhodamine B than the composite material prepared in Example 2, indicating that the abundant nanoneedle structure on the surface can provide more active sites for the photocatalyst, thereby improving the degradation performance.
[0096] Finally, a comparison was made with adding a photocatalyst alone (corresponding to...). Figure 6 The "No H2O2" in the text refers to the photocatalyst added here, which is the composite material prepared in Example 1, and the addition of only hydrogen peroxide solution (corresponding to...). Figure 6 The performance analysis of the "No catalysts" group shows that the combined effect of photocatalyst and hydrogen peroxide significantly improves the degradation performance.
[0097] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A Cu-Ag supported nano-Cu x The method for preparing O-Ag2O composite material is characterized by, Includes the following steps: S1. After melting gallium, it is coated onto the surface of copper and then annealed to obtain a Cu-Ga alloy; S2. The alloy precursor obtained by plating Ag on the surface of the Cu-Ga alloy obtained in step S1 is annealed again to form Cu-Ga-Ag alloy. S3. The Cu-Ga-Ag alloy obtained in step S2 is dealloyed to obtain a porous Cu-Ag substrate. S4. The porous Cu-Ag substrate obtained in step S3 is subjected to electrochemical oxidation to obtain the Cu-Ag supported nano-Cu. x O-Ag2O composite material; The Cu x The O-Ag2O composite material includes a porous Cu-Ag support and Cu atoms loaded on the surface of the porous Cu-Ag support. x O and Ag2O, where 1≤x≤2.
2. The preparation method according to claim 1, characterized in that, The Cu x O is a needle-like structure.
3. The preparation method according to claim 1, characterized in that, The Cu x O includes copper oxide and cuprous oxide.
4. The preparation method according to claim 1, characterized in that, The thickness of the porous Cu-Ag support is 20-60 μm.
5. The preparation method according to claim 1, characterized in that, In step S1, the annealing temperature is 100-250℃.
6. The preparation method according to claim 1, characterized in that, In step S2, the Ag plating method is vapor deposition, and the vacuum degree of the vapor deposition chamber is 5 × 10⁻⁶. -5 Pa.
7. The preparation method according to claim 1, characterized in that, In step S3, the specific steps for dealloying the Cu-Ga-Ag alloy include: placing the Cu-Ga-Ag alloy in an acidic solution and heating it for corrosion treatment for 2-8 hours.
8. The preparation method according to claim 1, characterized in that, In step S4, the electrochemical oxidation of the porous Cu-Ag substrate specifically includes the following steps: placing the porous Cu-Ag substrate in an alkaline solution, performing constant current oxidation under a DC power supply for 5-15 minutes, washing and drying the resulting sample with pure water to obtain Cu-Ag-loaded nano-Cu. x O-Ag2O composite material.
Citation Information
Patent Citations
Nano-porous copper loaded ultrafine oxide copper nanowire composite material and preparation method and application thereof
CN107366011A
Ag2O / CuO photocatalytic water oxidation catalyst
CN109550505A